Every Nation for Itself : Winners and Losers in a G-zero World - Bremmer, Ian (London Portfolio, 2013)
What happens when nobody's running the world? The US is in financial crisis and can't hold onto the reins of the G-20. Welcome to the G-Zero world, in which no single country has the power to shape a truly global agenda. The author reveals how world powers are rapidly turning into gated communities, locked in competition.
Include Notes and Index.
Winners and Losers in a G-zero World.
Keywords: World politics -- Economic development -- International cooperation